The Effectiveness of the Electromagnetic Trip Model as a Teaching Aid for Electrical Wiring Subjects - A. , Jamaat; Yee, M.H.; Tee, T.K.; Kok, B.C.; N. , Azid (International Journal of Psychosocial Rehabilitation, 2020)
Teaching Aids Tools are all the needs and equipment used by teachers and students to assist in the delivery and understanding of information. This study aims to test the effectiveness of Electromagnetic Trip model as teaching aids for Electrical Wiring Course at two Vocational Colleges (KV) and students’ perceptions of teaching aids used. The study design used is an experimental quasi. The KV involved are KV Setapak Kuala Lumpur (KVS) and KV Kuala Klawang Negeri Sembilan (KVKK). The study was divided into two groups of student’s namely KVS as the Treatment Group (KR) and KVKK as the Control Group (KK). Each group consists of 33 samples of the study. The research instrument used was pre-test and post achievement test to see the effectiveness of 'Electromagnetic Trip' model. The questionnaire was also used to examine students' perceptions of teaching aids. The results showed that the pre-test score of the two groups was at the same level and grade, which was a good level and obtained grade B. This shows that both groups are homogenoues. The results showed that there was a statistically significant difference between the post test score between KR (75.36%) and KK (68.73%). This shows that KR has a mean score of 5.57% and a level increase from grade B to grade B +. In addition, students are positively perceptive towards design, user-friendly, functional and acceptance and safety of the Electromagnetic Trip model used as teaching aids is very positive. In conclusion, the use of the Electromagnetic Trip model in PdPc can improve students’ achievement for Electrical Wiring subjects.